The Effect of Maternal Knowledge on the Prevention of Covid-19 Transmission at the Kota Pinang General Hospital - Saddiyah Rangkuti (Institute of Computer Science (IOCS), 2021)
On January 30, 2020, WHO designated COVID-19 as a Public Health Emergency of International Concern (PHEIC). Pregnant women are made a vulnerable group at risk of being infected with COVID-19 due to physiological changes during pregnancy (Liang, 2020). This study uses a pre-experimental type of research, with a One Group pre-test and post-test design. The population in this study were all pregnant women who were at the Kota Pinang General Hospital, the data collected in April-August were 20 people, The sample in this study was Purposive Sampling Technique, with the research technique using the Chi Square test. The results of this study indicate that there is an influence before being given knowledge of maternity mothers on the prevention of COVID-19 transmission at the Kota Pinang General Hospital in 2020 as many as 10 (50%) respondents fall into the poor category and after being given knowledge, there are 3 (15%) respondents. Meanwhile, before being given knowledge about preventing the transmission of COVID-19 to maternity mothers at the Kota Pinang General Hospital, 7 (35%) respondents were in the good category, and 12 (60%) respondents were in the good category after being given knowledge of maternity mothers on prevention of transmission. COVID-19. Based on the results of statistical tests using the Wilcoxon test, it is known that the p value (0.001) < (0.05) means that Ho is rejected, so it can be said that there is a significant influence regarding the effect of knowledge given to maternity mothers on the prevention of COVID-19 transmission at the Kota Pinang General Hospital in 2020. It is recommended to health workers, especially midwives, to provide counseling to maternity mothers regarding the prevention of COVID-19 transmission.